Computational modeling and experimental infrared spectroscopy of hydrogen bonding interactions in polyvinyl alcohol-starch blends - Lee, Tin Sin (Elsevier BV, 2010)
This study aims to investigate the hydrogen bonding interactions in polyvinyl alcohol (PVOH)–starch blends. Semi-empirical AM1 (Austin Model 1) and PM3 (Parameterized Austin Model 3) methods were employed to model the blending. Binding energies, vibrational frequencies and solubility parameters results were used to analyze the compatibility and stability of the blends. Besides that, experimental infrared spectroscopy was also conducted to validate the modeling results. The computed negative binding energies justified the stability of the blending. On the other hand, the solubility parameters of PVOH and starch modeling complexes have been found close to each other. This confirms that PVOH and starch are compatible blends. In addition, vibrational frequency analysis of these molecular complexes has exhibited that the hydroxyl group shifts to lower wavenumbers due to formation of hydrogen bonds. Findings from the experimental infrared spectroscopy have shown agreement with computational vibrational frequency results. The wavenumbers of the specimens increase is dependent on the ratios of PVOH in the blends. Such increment indicates that PVOH and starch interact in a harmonize manner and the blending is compatible.